Upaya Pemberdayaan UMKM Melalui Pelatihan Digital Marketing Di Desa Warureja - Wahid Wachyu Adi Winarto (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Micro, Small, and Medium Enterprises have an important role in Indonesia's economic growth, especially in Warureja Village. The purpose of the MSME empowerment activity through digital marketing training is to increase the knowledge of MSME actors in Warureja Village and to be able to market their products through digital platforms. The method used in this activity is to conduct a location survey and data collection of MSME actors in Warureja Village, then select activity ideas and implementation. In its implementation, the activity was attended by 54 participants. The factor that supports this activity is the increase in the knowledge of MSME actors regarding digital marketing. Then some factors that hinder this activity are coordination that has not been maximized and preparation that is so short that the data collection process has not been maximized. The benefits of this activity are increasing the knowledge of MSME actors in Warureja Village regarding digital marketing, thereby increasing the number of sales.